Marital Rape Sebagai Pelanggaran Hak Asasi Manusia - Titin Samsudin (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2010)
This article addresses the question of marital rape (rape in the household) or a rape that occurs between couples who tied with a legal marriage as a violation of humanrights. The impact of marital rape actions resulted in a huge effect on the victim, both physically and psychologically. There should be a healthy and naturalintercourse which is communicated between the two parties. Principally, a husband should not impose his will to his wife, especially in the matters of sexuality.Imposing the will means inhumanely treating couples and looking at nothing more than the fulfillment of sexual desire. Such deed is classified as an act of rape, namely rapping in marriage or the so-called the â€œmarital rapeâ€.